Modeling of piezoelectric laminated composite plate using finite element analysis - Mahmood, Iskandar Al-Thani; Khan, Md. Raisuddin (2004)
A finite element model for shape control analysis of piezoelectric laminated composite plate is presented in this paper. Elastic field and electric field of the piezoelectric laminated composite plate has been coupled through the linear piezoelectric constitutive equations. Piezoelectric actuators and sensors are modeled as additional layers either to be surface bonded or embedded in the laminated composite plate. A computer code was written in C++ based on the finite element model and was successfully validated with experimental and numerical results that are readily available in the literatures. The effects of actuator voltage, actuator orientation, fiber orientation and actuator placement along the thickness direction have been simulated and analyzed using the present model.